Should Heart Transplant Recipients with Early Graft Failure be Considered for Re-transplantation? - Iribarne, Alexander (2011)
BACKGROUND: The purpose of this study was to determine if orthotropic heart transplantation (OHT) performed within 90-days of an initial heart transplant (RETX) should be a contraindication to re-transplantation based on inferior outcomes when compared to primary OHT recipients (control). METHODS: De-identified data were obtained from the United Network for Organ Sharing. The study population included all adult heart transplant recipients > 18 years old from 1995–2008 (n=26,804). Multivariable regression was performed in order to assess the simultaneous effect of multiple risk factors on post-transplant graft failure at 90 days (PTGF). Secondary outcomes of interest included infection, stroke, and dialysis during the transplant hospitalization as well as primary non-function of the graft at 90 days. RESULTS: Among the study cohort, there were 90 (0.34%) RETX patients. Median survival in this group was 1.6 years compared to 10.5 years for controls. Unadjusted PTGF, infection, dialysis, and primary non-function was significantly higher (p<0.001) in the RETX group. After risk-adjustment, however, PTGF (p=0.545), infection (p=0.696), dialysis (p=0.664), stroke (p=0.115), and primary non-function (p =0.531), did not differ significantly between the two groups. CONCLUSIONS: When controlling for pre-transplant recipient characteristics, re-transplantation within 90 days of a previous transplant is not associated with increased morbidity or mortality. However, unadjusted overall survival was significantly worse in the RETX group. This suggests that although re-transplantation at 90 days alone is not a risk factor for inferior outcomes, given the significant comorbidities of these patients, the indications for re-transplantation within 90 days must be critically examined.